Kearifan Lokal Po Maa Masiaka dalam Kehidupan Masyarakat Buton - Tanzil Tanzil (Jurnal Neo Societal, 2025)
This research aims to examine the benefits of local wisdom po maa masiaka in the life of the Buton people and its preservation efforts. The research location in this study was carried out in Baubau City, Southeast Sulawesi Province. This research uses a qualitative approach, namely research that conducts an in-depth analysis of the object being studied. The selection of informants is carried out purposively, including community leaders and government representatives. The results of the study show that the local wisdom of po maa masiaka is one of the principles that underlie the social life of the community in the Buton community.  However, in the current era, the values of local wisdom po maa masiaka face quite significant challenges. The shift leads to a more individualistic lifestyle, and urbanization makes some of the younger generation less familiar with ancestral traditions. This study can provide recommendations. First, cultural education plays a very important role in efforts to preserve local wisdom po maa masiaka, in the form of instilling cultural values in the younger generation to form a character that respects the heritage of ancestors. Second, the Regional Government is expected to play an active role in preserving this local wisdom.